The contributions of search and human capital to earnings growth over the life cycle - Audra J. Bowlus; Huju Liu (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2012)
This paper presents and estimates a unified model where both human capital investment and job search are endogenized. This unification enables us to quantify the relative contributions of each mechanism to life cycle earnings growth, while investigating potential interactions between human capital investment and job search. Within the unified framework, the expectation of rising rental rates of human capital through job search gives workers more incentive to invest in human capital. In addition, unemployed workers reduce their reservation rental rates and increase their search effort to leave unemployment quickly to take advantage of human capital accumulation on the job. The results show both forces are important for earnings growth and the interactions are substantial: human capital accumulation accounts for 31% of total earnings growth, job search accounts for 46%, and the remaining 23% is due to the interactions of the two.
Keywords: J24; J64; D91; 330; Human Capital; Job Search; Life Cycle; Earnings Growth